The methodological basis and applicability of a regional ICT index - Botos, Szilvia (Acta Agraria Kaposváriensis, 2011)
Access networks are important part of ICT sector. Its speed essentially defines the utility of the system. In Hungary, in 2009 the average guaranteed download speed was just 1 Mbit/s, and a little more than the tenth part of subscribers had 4 Mbit/s or more data rate. Only broadband – capacity of at least 50 Mbit/s – infrastructure is suitable for the satisfaction of claims of immediate future. It is not provided by the own investments of service providers, which based on business, so in regions, which less attractive commercially, state intervention is necessary. Although EU support also available, it is not enough to the necessary developments. Therefore would be worthy to select the target of developments on the basis of usefulness aspects. My aim is to rank regions based on the ICT development of them, because it is worthy to focus time and resources, where these will be return as quickly as possible. In this case it is important to take into consideration such socio-economic factors, which really correlate with existence of broadband networks. In this article I present NRI (Networked Readiness Index) which is the basis of my index and I sketch the planned scope of economical, technological and social data which can be involved in my index and they correlate with effects of broadband networks.